2013
DOI: 10.2337/dc12-0919
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Fok-I Polymorphism Modulates Diabetic Host Response to Vitamin D Intake

Abstract: OBJECTIVEInterpopulation as well as interindividual variations in response to vitamin D intake commonly observed in subjects with type 2 diabetes may be related to genetic makeup. One of the candidate genes potentially responsible for this diversity is vitamin D receptor (VDR). This study aimed to investigate the interactive effect of VDR Fok-I polymorphism and vitamin D intake on diverse aspects of diabetic host response.RESEARCH DESIGN AND METHODSGlycemic status, lipid profiles, inflammatory biomarkers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 38 publications
3
61
6
Order By: Relevance
“…We found that VDR FokI ff were 'low-responders' to vitamin D in terms of rise in circulating 25(OH)D and amelioration of some inflammatory markers, including highly sensitive C-reactive protein (hsCRP) and IL-6 [48]. However, further analyses revealed no between-group difference in changes of TAC, MDA, GSH, SOD and GSH-Px among VDR FokI genotypes.…”
Section: Antioxidant Effect Of Vitamin D In Diabetes: Direct Vs Indicontrasting
confidence: 45%
See 1 more Smart Citation
“…We found that VDR FokI ff were 'low-responders' to vitamin D in terms of rise in circulating 25(OH)D and amelioration of some inflammatory markers, including highly sensitive C-reactive protein (hsCRP) and IL-6 [48]. However, further analyses revealed no between-group difference in changes of TAC, MDA, GSH, SOD and GSH-Px among VDR FokI genotypes.…”
Section: Antioxidant Effect Of Vitamin D In Diabetes: Direct Vs Indicontrasting
confidence: 45%
“…While the recent recommended dietary allowance (RDA) for vitamin D has been increased to 600 IU (from a previously recommended dosage of 400 IU), most experts still believe this amount would be insufficient to make desirable serum levels of 25(OH)D of 75-100 nmol/L, so they recommend a daily intake of 400-1000 IU/d for children under 1y, 600-1000 IU/d for children 1-18y, and 1500-2000 IU/d for adults [5]. The requirement in diabetic carriers of certain genotypic variants (like VDR FokI ff) may prove to be even higher [48]. The method of determination of circulating 25(OH)D is another issue of concern.…”
Section: Resultsmentioning
confidence: 92%
“…A genome-wide study revealed that allelic variants of several genes involved in vitamin D metabolism and transport are associated with serum levels of 25-hydroxyvitamin D [60 ] . Some, but not all, candidate gene studies also found associations between genetic variants and the response to vitamin D supplements, and more research is needed to clarify this issue [61][62][63][64] .…”
Section: Genetic Factors Influencing Drug Responsementioning
confidence: 99%
“…If the initiating translation starts from this alternative site (thymine variant), it results in the generation of a longer VDR protein of 427 amino acids (Kostner et al, 2009). The polymorphisms in this area have been studied singly and in combination with other polymorphisms of VDR in a number of malignant and non malignant conditions (Chiu et al, 2001;Malecki et al, 2003;Park et al, 2006;Kadyska et al, 2007;Hubner et al, 2008;Neyestani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%